Individual identification and population assignment with microsatellite markers in three Indian donkey populations - BEHL, RAHUL; NIRANJAN, S K; BEHL, JYOTSNA; VIJH, R K (The Indian Journal of Animal Sciences, 2020)
Ability of the microsatellite markers for individual identification and their potential for breed assignment of individuals was evaluated in three Indian donkey populations. The probability of identity of two random individuals within a population (G1), taking into consideration all eleven loci was 5.91×10–13, 1.06×10–12 and 3.67×10–14 in Ladakhi, Spiti and Andhra-brown donkeys, respectively. Similarly, the probability of identity of two random individuals from two different populations (G2) between Spiti and Ladakhi donkeys, the two most closely related populations, was only 8.05×10–21 . However, the population assignment precision using this set of 11 loci, the correct assignments ranged between 73.08 (Andhra-brown) to 96% (Ladakhi) with frequency method and between 88.46 (Andhra-brown) to 100% (Ladakhi) with Baysian approach. These results suggest that this set of markers can be a promising tool for identification of individuals and their products. Although G2 values were higher than the G1 values but when this set was specifically evaluated for breed allocation purposes, our results indicated that it may require further substantiation before this set can be safely employed for breed/population allocation of individuals in Indian donkey populations.